Profile of Guided Discovery Learning Implementation Assisted by Virtual Lab and Students’ Problem-Solving Skills on Gas Kinetic Theory - Abib Hani Mashurin; Husni Mubarok; Binar Kurnia Prahani (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This research was conducted to obtain a guided discovery learning implementation profile with virtual lab assistance and problem-solving skills for high school students on gas kinetic theory. The type of research was descriptive preliminary research, without hypothesis testing. The research subjects consisted of 106 students in senior high school. This study used qualitative descriptive analysis from questionnaires and online tests. This study revealed that the level of students’ problem-solving skills was low. This case was proven by 102 students (27 male; 75 female) in the low category with a score range of 0 to 45, and four students in the moderate category with a score range of 46 to 75, while there were no students in the high category with a score range of 76 to 100. This research implies that there is a need for a guided discovery learning model with the help of a virtual lab to analyze the problem-solving skills of high school students, especially on gas kinetic theory.